Mouse TRIP13/PCH2 Is Required for Recombination and Normal Higher-Order Chromosome Structure during Meiosis - Roig, Ignasi (Public Library of Science, 2010)
Accurate chromosome segregation during meiosis requires that homologous chromosomes pair and become physically connected so that they can orient properly on the meiosis I spindle. These connections are formed by homologous recombination closely integrated with the development of meiosis-specific, higher-order chromosome structures. The yeast Pch2 protein has emerged as an important factor with roles in both recombination and chromosome structure formation, but recent analysis suggested that TRIP13, the mouse Pch2 ortholog, is not required for the same processes. Using distinct Trip13 alleles with moderate and severe impairment of TRIP13 function, we report here that TRIP13 is required for proper synaptonemal complex formation, such that autosomal bivalents in Trip13-deficient meiocytes frequently displayed pericentric synaptic forks and other defects. In males, TRIP13 is required for efficient synapsis of the sex chromosomes and for sex body formation. Furthermore, the numbers of crossovers and chiasmata are reduced in the absence of TRIP13, and their distribution along the chromosomes is altered, suggesting a role for TRIP13 in aspects of crossover formation and/or control. Recombination defects are evident very early in meiotic prophase, soon after DSB formation. These findings provide evidence for evolutionarily conserved functions for TRIP13/Pch2 in both recombination and formation of higher order chromosome structures, and they support the hypothesis that TRIP13/Pch2 participates in coordinating these key aspects of meiotic chromosome behavior.